Potential of Steinernema abbasi, Steinernema siamkayai and Heterorhabditis indica for the biomanagement of tobacco cutworm - ., Istkhar; Chaubey, A K (Indian Journal of Plant Protection, 2020)
The intensive use of insecticides for the control of Spodoptera litura has resulted in development of resistance against several insecticides in many parts of the world, making it as one of the world’s most severe insect pests. In the present study, three species of entomopathogenic nematodes, Steinernema abbasi, S. siamkayai and Heterorhabditis indica were used for their insecticidal properties against fourth stage S. litura larvae. Results showed the high virulence of these nematodes as they killed all the larvae of S. litura within 48 to72 hours. S. abbasi killed all the larvae when applied at doses of 100 and 200 infective juveniles (IJs)/larva within 36 hours and in 48 hours in all other concentrations whereas larvae infected with S. siamkayai were found dead at a dose of 200 (IJs)/larva within 48 hours and in 72 hours in all other concentrations. In H. indica treated larvae, all the larvae were killed within 24 hours at an applied dose of 200 IJs/larva and in 48 hours in other concentrations. Low lethal concentration and lethal time values obtained from assays with S. abbasi and H. indica indicate that they are highly virulent to S. litura larvae where only six and five IJs were enough to cause 50% population to die within 36 hours. S. abbasi was found to possess highest reproductive potential with a value of 38±5.6×103 IJs/larva followed by S. siamkayai and H. indica.